The emerging LGBTI rights challenge to transitional justice in Latin America - Bueno-Hansen, Pascha (International journal of transitional justice, 2018)
Latin American truth commissions have recently expanded their purview to include cases of violence against gender and sexual minorities as human rights violations worthy of investigation. This article proposes that grappling with this emerging LGBTI (lesbian, gay, bisexual, transgender and intersex) rights challenge requires a queer, intersectional and decolonial analytical lens that underscores the relevance of global LGBTI politics, and critiques transitional justice foundational assumptions regarding temporality and binary logics. In practical terms, this analytical lens enacts a double move by unearthing the deeply tangled and life-extinguishing roots of impunity surrounding violence against gender and sexual minorities while advocating for the realization of LGBTI people’s full citizenship.